2018
DOI: 10.14419/ijet.v7i2.10.10968
|View full text |Cite
|
Sign up to set email alerts
|

Item analysis on the effects of study visit programme in cultivating students’ soft skills: A case study

Abstract: Experiential learning programme is an important platform in the process of cultivating student's self-development. The teaching approaches that apply experiential learning are widely implemented in higher education. The Faculty of Education in UTM has organised many of such experiential learning activities for students, however the effect of the programmes towards students' self-development is still under researched. Hence, it is still unable to fully identify their effects on cultivating students' soft skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Conversely, Mustikawati et al (2016) argue that since developing soft skills is not based on technical knowledge alone, it cannot be taught but instead needs repeated practice under mentorship. Although academic achievement should remain a primary focus within higher education institutions, graduates must also demonstrate competence in essential soft skills like leadership ability, communication prowess, and teamwork competency (Rameli et al, 2018). Henceforth it can be inferred that Soft Skills enable, catalyze, and facilitate effective attitudes, social behaviors, and competencies (Ratka&Pharm,2018).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Mustikawati et al (2016) argue that since developing soft skills is not based on technical knowledge alone, it cannot be taught but instead needs repeated practice under mentorship. Although academic achievement should remain a primary focus within higher education institutions, graduates must also demonstrate competence in essential soft skills like leadership ability, communication prowess, and teamwork competency (Rameli et al, 2018). Henceforth it can be inferred that Soft Skills enable, catalyze, and facilitate effective attitudes, social behaviors, and competencies (Ratka&Pharm,2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is observed that the interrelationship between Soft Skills and Engineering is the dimension most approached in the literature (123 articles), followed by Professional Ethics and Engineering (35 articles). However, the interrelation between Professional Ethics and Soft Skills presents only one publication, by Rameli et al (2018), in which the authors, through a case study, analyze how learning activities based on experimentation contribute to the development of Soft Skills, as Professional Ethics.…”
Section: Bibliometric and Descriptive Analysismentioning
confidence: 99%